Analysis of Student's Kinesthetic Activities Against Understanding the Principles of DSSC Work - Cahyani, Nur; Darsikin, Darsikin; Saehana, Sahrul (Jurnal Riset Pendidikan MIPA, 2019)
This study aims to determine how students 'kinesthetic learning activities on understanding the DSSC work principles and to determine the effect of students' kinesthetic activity processes on understanding the working principles of DSSC at Tadulako University. This research was a descriptive-qualitative study where all data is collected based on facts obtained in the field to produce descriptive data in the form of written or spoken words from the people being observed. Respondents involved in this study were 42 students. Data obtained through activity activities, interview comprehension tests, and questionnaires. The results showed that students had been learning kinesthetic activities very well, through kinesthetic activities students became more active students and felt happy. This was reinforced by active discussion, test results where most students got good grades, and interviews. It can be seen that although students' learning styles differ if the kinesthetic learning style was applied, students can easily remember and understand if they do this directly, this was reinforced by a questionnaire. The information obtained by kinesthetic learning styles complements learning styles in addition to kinesthetic.